Good Governance: Importance in Practice, Theories and Definitions - Addink, G. H. (Halu Oleo Law Review, 2017)
This work addresses at exploring appropriate method in applying the principle of good governance; importance in practice, theories and definitions. This effort is importance to understand in more detail the three dimensions of good governance. The relationship between good governance and national prosperity is not always clear and opinions vary across countries. But it is seen that good governance is important for the economic and social development of countries and promotion of good governance also creates more open and democratic societies. For that reason, this work offers the three dimensions of good governance: the rule of law, the democracy, and the institutional dimension. The solution of this method would precisely construct a holistic and integrated strategy in managing and optimizing collective strategic resources.This work addresses at exploring appropriate method in applying the principle of good governance; importance in practice, theories and definitions. This effort is importance to understand in more detail the three dimensions of good governance. The relationship between good governance and national prosperity is not always clear and opinions vary across countries. But it is seen that good governance is important for the economic and social development of countries and promotion of good governance also creates more open and democratic societies. For that reason, this work offers the three dimensions of good governance: the rule of law, the democracy, and the institutional dimension. The solution of this method would precisely construct a holistic and integrated strategy in managing and optimizing collective strategic resources.